Effects of angiotensin II in the management of perioperative hypotension in kidney transplant recipients. Issue 9 (19th July 2022) - Andrews, Lauren; Benken, Jamie; Benedetti, Enrico; Nishioka, Hokuto; Pierce, Dana; Dalton, Kaitlyn; Han, Justin; Shin, Bona; Benken, Scott
Abstract: Background: Due to the mechanisms of action of conventional catecholamine vasopressors, there is increased risk of renal allograft injury and adverse events in transplant recipients with fluid‐refractory distributive shock during the perioperative period. As such, mechanistically alternative vasopressors like angiotensin II (ATII) may avoid these complications, but there is an absence of data supporting use in this population. Methods: This was a single‐center, single‐arm, open‐label, phase 4 study conducted as a 1‐year pilot of 20 adult renal transplant recipients receiving ATII as their first continuous infusion vasopressor in the perioperative period. The study aim was to systematically assess the safety and hemodynamic effects of ATII. Safety was assessed based on the incidence of adverse events. Hemodynamic effect was assessed by the achievement of per protocol hemodynamic goals (i.e., SBP ≥120 mmHg) and the need for adjunct vasopressors. Results: Most cases involved deceased donors (70%), with a corresponding mean (SD) cold ischemia time of 14.7 (8.6) h. Over a surgery duration of 5.3 (1.2) h, subjects received 3.2 (2.0) L of total volume resuscitation prior to ATII initiation. No adverse events were directly related to ATII administration. Throughout this period, ATII was utilized for a median of 1.0 (IQR, 1.5) h intraoperatively ( N  = 7), 26.5 (IQR, 84.8) h postoperatively ( N  = 4), and 63.8 (IQR, 57.8) h in subjects who required ATII both intra‐ and postoperatively ( N  = 9). Only one of the 20 patients needed adjunct continuous infusion vasopressors in addition to ATII. Conclusions: Based on the observations of this pilot study, ATII is a safe and effective vasopressor option for renal transplant recipients requiring perioperative hypotension reversal.